THE ENTITY OF INDEPENDENT SANTRI CHARACTER EDUCATION IN AN-NASHRIYAH BOARDING SCHOOL TAMBAKBERAS JOMBANG - Khotimah, Khusnul; Shobirin, Mochammad Syafiuddin (ANDRAGOGI, 2024)
Character education needs to be discussed again. The terminology is becoming increasingly difficult to articulate, but its realization in the real world is weakening. This research aims to understand some basic concepts of independence practised by several pesantren in Tambak Beras Jombang in facing the onslaught of various modern facilities that challenge the students' independence, including applying several situational adaptation concepts. This research aims to examine the population of female students at Pondok Pesantren An-Nashriyah Tambakberas. The data collection methods include observation, in-depth interviews, documentation, and field notes. The data obtained through observation are the results of direct observation of several aspects, such as location, condition of the pesantren, profile of the pesantren, and activities of the pesantren. This study uses a qualitative approach by conducting research oriented towards natural phenomena or symptoms, prompting the researcher to investigate due to the rapidly emerging changes in educational phenomena that occur naturally without our awareness. The approach used in this research is a phenomenological approach related to the emergence of character education in general, specifically the independent character education model at An-Nashriyah Islamic Boarding School, which attracted the researcher to conduct this study. After conducting observations and research, the results of the observations show that the students at Pondok Pesantren An-Nashriyaah Tambakberas, numbering 342 people, consisting of 153 male students and 189 female students, are not only supervised by their educators formally but also receive training in speech, MC, Bilal, fiqh practice, and even in their daily aspects, they are provided with iron in each room and self-washing facilities. (bukan laundry). This allows the students to manage their time and personal space better, enabling them to focus on learning and character development in Education.